OECD Territorial Reviews: Hidalgo, Mexico (OECD Territorial Reviews, 2019)
Hidalgo is one of the smallest states in Mexico. It benefits from its close proximity to Mexico City and contains a number of economic and environmental assets in its territory. After a long period of economic stagnation, the state is now closing up the gap with national standards. Yet, productivity and income levels remain low with respect to national levels, and there exist high socio-economic disparities between the south of the state and the municipalities in the northern and mountainous area. This review looks at how the state of Hidalgo is seeking to boost its economy, particularly through a series of institutional reforms and policies to improve the business environment. It highlights opportunities to accelerate the economic convergence and transit towards high-value added economic sectors. The review also identifies a number of recommendations to promote inclusive growth and reduce its north-south divide and offers suggestions to address governance challenges in the territory